▼Meropenem - an advantageous antibiotic?. Issue 7 (July 1996) - Unknown
Abstract : Meropenem (Meronem - Zeneca) follows imipenem1 as the second carbapenem β-lactam antibiotic to be marketed in the UK. Does meropenem offer therapeutic advantages, particularly when compared with imipenem?